The calcium-sensing receptor stabilizes podocyte function in proteinuric humans and mice - Mühlig, Anne K.; Steingröver, Johanna; Heidelbach, Hannah S.; Wingerath, Madelaine; Sachs, Wiebke; Hermans-Borgmeyer, Irm; Meyer-Schwesinger, Catherine; Choi, Hoon Young; Lim, Beom Jin; Patry, Christian; Hoffmann, Georg F.; Endlich, Nicole; et al. (Kidney international)
Calcimimetic agents allosterically increase the calcium ion sensitivity of the calcium-sensing receptor (CaSR), which is expressed in the tubular system and to a lesser extent in podocytes. Activation of this receptor can reduce glomerular proteinuria and structural damage in proteinuric animal models. However, the precise role of the podocyte CaSR remains unclear. Here, a CaSR knockdown in cultured murine podocytes and a podocyte-specific CaSR knockout in BALB/c mice were generated to study its role in proteinuria and kidney function. Podocyte CaSR knockdown abolished the calcimimetic R-568 mediated calcium ion-influx, disrupted the actin cytoskeleton, and reduced cellular attachment and migration velocity. Adriamycin-induced proteinuria enhanced glomerular CaSR expression in wild-type mice. Albuminuria, podocyte foot process effacement, podocyte loss and glomerular sclerosis were significantly more pronounced in adriamycin-treated podocyte-specific CaSR knockout mice compared to wild-type littermates. Co-treatment of wild-type mice with adriamycin and the calcimimetic cinacalcet reduced proteinuria in wild-type, but not in podocyte-specific CaSR knockout mice. Additionally, four children with nephrotic syndrome, whose parents objected to glucocorticoid therapy, were treated with cinacalcet for one to 33 days. Proteinuria declined transiently by up to 96%, serum albumin increased, and edema resolved. Thus, activation of podocyte CaSR regulates key podocyte functions in vitro and reduced toxin-induced proteinuria and glomerular damage in mice. Hence, our findings suggest a potential novel role of CaSR signaling in control of glomerular disease.
Gesehen am 25.09.2022